PENGUATAN KELEMBAGAAN ZAKAT DI INDONESIA MELALUI SINERGI FIKIH DAN MANAJEMEN: TINJAUAN KONSEPTUAL DAN STRATEGIS - divantori, muaffa rizqi (Maliki Interdisciplinary Journal, 2025)
The management of zakat in Indonesia faces significant institutional challenges, including weak regulatory enforcement, limited human resources, and low public participation. Yet, zakat holds great potential as a means of wealth redistribution and economic empowerment for Muslim communities. This conceptual article aims to explore strategies for strengthening zakat institutions through the integration of Islamic jurisprudence (fiqh) and modern management principles. The study employs a conceptual analysis, theoretical development, and conceptual modeling approach. The findings indicate that managerial principles such as strategic planning, transparency, accountability, and the utilization of digital technology can harmoniously align with the values of fiqh and the objectives of Islamic law (maqāṣid al-sharī‘ah). This integration is essential for building zakat institutions that are professional, trustworthy, and impactful. The article recommends regulatory reform, amil certification, digitalization of zakat information systems, and community-based zakat literacy as key strategies for strengthening the national zakat framework.